Father André Scrima on Interdenominational Dialogue and Interreligious Openness - Boicu, Dragoş (Religions, 2021)
Living and teaching among different cultures, Father André Scrima found a favourable environment that challenged him to understand the complex dynamic of the relationship with the ‘alien’, the ‘other’. He developed a fresh theological position and proposed a responsible openness to otherness. Through his entire diplomatic and didactic activity, and especially through the ideas he promoted in his courses, he tried to set in motion an approach to interfaith and interreligious dialogue that was as humble as possible, but creative and free. The purpose of this paper is to present, as authentically as possible, a part of his outstanding thinking on the matter of interdenominational dialogue and interreligious openness.